Paralympic Sport Management System (PSMS) / Chan Foo Keong - Chan , Foo Keong (2001)
Paralympic Sport Management System (PSMS) is a management information system that will manage the Paralympic sport organized by Malaysian Paralympic Council (MPC). PSMS utilize the web-based technologies to perform as an intranet system and will replace the current manual system in MPC. PSMS wilt integrate with another two system and the system was named as Paralympic lnformation and Management System (PIMS). The two systems are: Paralympic One-Stop Center, an internet system and Paralympic Athletes Management System, an intranet system. PSMS has been divided to three section, administrator section, assistant administrator section and user section. The administrator section will allow the administrator to create new database for a new Paralympic sport event. While, the assistant administrator will maintain the volunteers' information, create the committee structure for the sport event, generate the technical competition report, and arrange the schedule and venue for eve1y game type. The technical competition report includes the equipment and result management. Finally, the user section contains only one module, which is the search module to provide search engine when access to the system. It is believed that final product will able to provide a systematic and reliable management information system for MPC.